Glutamine synthetase type I (glnAI) represents a rewarding molecular marker in the classification of bifidobacteria and related genera - Killer, Jiří; Mekadim, Chahrazed; Bunešová, Věra; Mrázek, Jakub; Hroncová, Zuzana; Vlková, Eva (Folia microbiologica, 2020)
The family Bifidobacteriaceae constitutes an important phylogenetic group that particularly includes bifidobacterial taxa demonstrating proven or debated positive effects on host health. The increasingly widespread application of probiotic cultures in the twenty-first century requires detailed classification to the level of particular strains. This study aimed to apply the glutamine synthetase class I (glnAI) gene region (717 bp representing approximately 50% of the entire gene sequence) using specific PCR primers for the classification, typing, and phylogenetic analysis of bifidobacteria and closely related scardovial genera. In the family Bifidobacteriaceae, this is the first report on the use of this gene for such purposes. To achieve high-value results, almost all valid Bifidobacteriaceae type strains (75) and 15 strains isolated from various environments were evaluated. The threshold value of the glnAI gene identity among Bifidobacterium species (86.9%) was comparable to that of other phylogenetic/identification markers proposed for bifidobacteria and was much lower compared to the 16S rRNA gene. Further statistical and phylogenetic analyses suggest that the glnAI gene can be applied as a novel genetic marker in the classification, genotyping, and phylogenetic analysis of isolates belonging to the family Bifidobacteriaceae.
Keywords: genotyp; Glutamate-Ammonia Ligase; Genotype; RNA ribozomální 16S; glutaminsynthetasa; Genes, Bacterial; Bacterial Typing Techniques; sekvenční analýza DNA; techniky typizace bakterií; Sequence Analysis, DNA; fylogeneze; bakteriální geny; DNA bakterií; genetické markery; DNA Primers; DNA, Bacterial; RNA, Ribosomal, 16S; Genetic Markers; DNA primery; Phylogeny; Bifidobacterium